Assessing the Risk Factors for Musculoskeletal Disorders in Construction Workers Using PATH, Case Study: Construction Project - Shaban parhani; Ramazan Mirzaei; Hussein Ansari (Iranian Journal of Health, Safety and Environment, 2017)
Construction workers experience a high risk of developing musculoskeletal disorders due to the nature of their jobs. This article aimed to evaluate the risk factors of musculoskeletal disorders among construction workers using Posture, Activity Tools and Handling (PATH). This is a sectional, descriptive-analytical study in a construction site in Tehran, Iran. Certain factors were identified namely body posture, weight of carried tools and objects, activities and tools, and their tasks and activities using PATH. PATH sheets were coded for a certain job. Descriptive data and Chi-square test were employed to analyze the data using SPSS.19. Identification and evaluation were performed in three most important stages of construction: foundation, carcass, finishing (elaborate work). The mean age was 33.08±8.97. Body posture included gentle bending posture (21.2%), severe bending (8.2%), bending and twisting (7% and 1.9%, respectively). Body positions, feet, hands, and weight of tools and objects were significantly different in the working stages (P